Analisis Konten mengenai Pengalaman Emosional Emerging Adults terkait Ghosting pada Hubungan Romantis - Widiastuti, Ratih; Saputra, Dinar; Rizka, Cut Mellyza; Fitri Apriliana, Novita (Universitas Paramadina, 2025)
Ghosting, which is defined as the sudden termination of communication without explanation, has become increasingly common in romantic relationships in the digital era. This behavior is often seen as a tactic for ending relationships. The study assessed the participants' emotions during the ghosting event, their current emotional refletions, and the factors and effects associated with ghosting. A qualitative approach was used, employing inductive content analysis to examine the participants'narratives and understand their emotional experiences based on their roles. The study involved 78 participants aged 19 to 25 who had experienced either ghosting other or being ghosted. Respondents were categorized into two groups: ghosters (those who ghosted others), ghostee (those who were ghosted). The findings reveal that emotional experiences vary significantly depending on one's role. Both ghosters and ghostees generally expressed similiar emotions, such as sadness, anger, and calmness during the event. However, guilt and relief were more commonly reported among ghosters, depending on the reasons for their behavior. In contrast, ghostees predominantly expressed feelings of sadness and hurt. The impacts felt by ghostees included diminished self-worth, emotional loneliness, and a decreased willingness to enter new relationships. This study underscores the impotance of interdisiplinary approaches to understanding ghosting, aiming promote healthier, safer, and more sustainable romantic relationships in the digital era.